Growth and Yield of White Sandal (Santalum Album L.) in South West Bengal - Das, Sudhir Chandra (Indian Forester, 2013)
West Bengal has patches of sandal trees mainly in and around Range and Beat Office compounds of South West Bengal to ensure protection. Information on growth pattern of the species would be of immense help in evaluating the expected yield. Height and girth of standing sandal trees and 51 felled trees was taken in Hirbundh Beat of Khatra range of Bankura (South) Division, West Bengal. A sandal wood tree attained an average height of 10.20 m and girth of 83.00 cm at the ageof 35 years. A average yield per tree was recorded 214.51 kg and av. price per tree was 1,90,000.00 while maximum yield recorded from one tree was 415 kg which fetched a avenue of 4,35,000.00 in 2010. It indicate considerable scope of sandal wood cultivation in West Bengal in the place where proper protection is ensured.